2002
DOI: 10.1071/ar02002
|View full text |Cite
|
Sign up to set email alerts
|

Performance of purebred and crossbred rabbits in Australia: doe reproductive and pre-weaning litter traits

Abstract: Data from a rabbit breeding experiment were analysed to compare the doe reproductive and pre-weaning litter performance of 3 breeds of rabbits, namely New Zealand White (N), Californian (C), and Flemish Giant (F), and their crosses CN (C × N) and FN (F × N). The foundation stock of 152 rabbits was collected from 26 different sources in New South Wales, Australia. Data on reproductive traits, doe age at first successful mating (DA), doe weight at first successful mating (DW) arising from 104 does, conception ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
2
4
1
1
Order By: Relevance
“…The general lack of influence of heterosis on disease incidence in this study may be due to less genetic isolation between the breeds of rabbits or simply because there is no consistent heterosis effect for this trait. There was no significant heterosis observed in the breed crosses in this population (Prayaga and Eady, 2003) for individual growth and slaughter traits but significant levels of heterosis were observed for doe reproductive traits in one breed cross (Prayaga and Eady, 2002).…”
Section: Time Of Deathcontrasting
confidence: 45%
“…The general lack of influence of heterosis on disease incidence in this study may be due to less genetic isolation between the breeds of rabbits or simply because there is no consistent heterosis effect for this trait. There was no significant heterosis observed in the breed crosses in this population (Prayaga and Eady, 2003) for individual growth and slaughter traits but significant levels of heterosis were observed for doe reproductive traits in one breed cross (Prayaga and Eady, 2002).…”
Section: Time Of Deathcontrasting
confidence: 45%
“…Hamouda et al [ 17 ] reported litter size value of 8.50 at first generation with Hyla rabbits in Tunisia. The litter size at birth in this study were also lower than 8.3 reported as average in different rabbit breeds in Australia [ 18 ], but closer to 6.30 recorded with New Zealand White rabbits in USA [ 19 ]. Litter size at birth obtained from this study were within the range reported by Kabir [ 20 ] for pure bred rabbits in Nigeria but lower litter size at weaning compared to values obtained in this study.…”
Section: Discussionsupporting
confidence: 73%
“…The average kit weight at birth obtained in this study, were 47.19, 50.95, 47.99 and 45.51 in Fauve de Bourgogne, Chinchilla, British Spot and New Zealand White, respectively, compared to other authors; the average weights of kits at birth were 58.1 g and 60.2 g [ 18 ] in Australia, 43.7 g in Sudanese rabbits [ 21 ] and 62.07 g reported by Karikari et al [ 22 ] in Ghana. Akinsola [ 14 ] reported higher weaned kits’ weight than the value recorded in similar Hyla rabbit in Tunisia [ 17 ], Egypt [ 23 ] and Chrystosome et al [ 16 ] in Benin.…”
Section: Discussionsupporting
confidence: 46%
“…These results support those reported by Ouyed et al (2007) with regard to LW63 which decreased after the 4 th litter. Also, Prayaga and Eady (2003) reported that the individual body weights at 5 and 10 wk of age were significantly lower in the 1 st parity born rabbits than in other higher parity born rabbits. However, they reported significantly higher carcass weights in the 2 nd and 3 rd parity litters than in 1 st and 4 th ones.…”
Section: Fixed Effects Of Parity Litter Size Time Period and Sexmentioning
confidence: 99%
“…Breed type differences for carcass traits have often been reported (Lukefahr et al, 1983;Ozimba and Lukefahr, 1991;Nofal et al, 2004). Prayaga and Eady (2003) reported that CA purebreds and crossbreds had the lowest performances, both for growth and slaughter traits, except for dressing out percentage. Lukefahr et al (1983) also reported higher dressing percentage in rabbits coming from CA lines when compared to the NZ lines, although our findings did not coincide with these results.…”
Section: Genetic Types and Dickerson's Parameter Estimatesmentioning
confidence: 99%